2019
DOI: 10.3390/v11090803
|View full text |Cite
|
Sign up to set email alerts
|

Faecal Virome Analysis of Wild Animals from Brazil

Abstract: The Brazilian Cerrado fauna shows very wide diversity and can be a potential viral reservoir. Therefore, the animal’s susceptibility to some virus can serve as early warning signs of potential human virus diseases. Moreover, the wild animal virome of this biome is unknown. Based on this scenario, high-throughput sequencing contributes a robust tool for the identification of known and unknown virus species in this environment. In the present study, faeces samples from cerrado birds (Psittacara leucophthalmus, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 96 publications
(115 reference statements)
2
47
2
1
Order By: Relevance
“…Type 1 was found to occur in Senegal parrot, red‐fronted parrot, and red‐breasted parakeet, whereas PsAdV‐4 originated from red‐bellied parrot . Additional aviadenovirus sequences, obtained from Meyer’s parrot, white‐eyed parakeet , four different falcon species (Aplomado falcon, American kestrel, orange‐breasted falcon, Teita falcon), gull, and Humboldt penguin , as well as neotropic cormorant were also published. Metagenomics study of crane fecal samples revealed almost the complete genome sequence of a new aviadenovirus with a surprisingly low (34%) G+C content .…”
Section: Advs In Birds (Aviadenovirus Atadenovirus Siadenovirus)mentioning
confidence: 99%
“…Type 1 was found to occur in Senegal parrot, red‐fronted parrot, and red‐breasted parakeet, whereas PsAdV‐4 originated from red‐bellied parrot . Additional aviadenovirus sequences, obtained from Meyer’s parrot, white‐eyed parakeet , four different falcon species (Aplomado falcon, American kestrel, orange‐breasted falcon, Teita falcon), gull, and Humboldt penguin , as well as neotropic cormorant were also published. Metagenomics study of crane fecal samples revealed almost the complete genome sequence of a new aviadenovirus with a surprisingly low (34%) G+C content .…”
Section: Advs In Birds (Aviadenovirus Atadenovirus Siadenovirus)mentioning
confidence: 99%
“…Moutelíková et al [34] show the emergence of rare bovine-human reassortant DS-1-Like rotavirus A strains in human patients in the Czech Republic. Duarte et al [35] present the virome of different wild birds and mammals from Brazilian cerrado, showing sequences of members of Adenoviridae, Anelloviridae, Circoviridae, Caliciviridae, and Parvoviridae families, complete or nearly complete genomes of known anelloviruses, circoviruses, and parvoviruses, as well as putative novel species.…”
mentioning
confidence: 99%
“…However, our study shows that GyV11 can be dispersed by the faeces of, at least, two different avian species (Myrmeciza ferruginea and Pithys albifrons) and is likely circulating among different bird species within the same community. In fact, in a closer area such as Brazil, the circulation of a phylogenetically close genotype (GyV4) has been detected in chickens and three other gyroviruses (CAV, GyV2, and GyV3) have been found in the fecal virome of wild birds [3,36].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous novel viruses and virus variants have been discovered by virus metatranscriptomics and metagenomics in different bird species, mainly in wild birds [1][2][3]. Nevertheless, there is still very little known about viruses that circulate in wild birds, especially…”
Section: Introductionmentioning
confidence: 99%